2019
DOI: 10.3390/ijms20246184
|View full text |Cite
|
Sign up to set email alerts
|

Newly Developed CK1-Specific Inhibitors Show Specifically Stronger Effects on CK1 Mutants and Colon Cancer Cell Lines

Abstract: Protein kinases of the CK1 family can be involved in numerous physiological and pathophysiological processes. Dysregulated expression and/or activity as well as mutation of CK1 isoforms have previously been linked to tumorigenesis. Among all neoplastic diseases, colon and rectal cancer (CRC) represent the fourth leading cause of cancer related deaths. Since mutations in CK1δ previously found in CRC patients exhibited increased oncogenic features, inhibition of CK1δ is supposed to have promising therapeutic pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…When comparing the IC 50 data provided in Table 2 , it has to be considered that, as expected, our calculated IC 50 values for PF-670462, Liu-20 and PF-4800657 differ from the previously published IC 50 values of 13 nM for PF-670462 and CK1δ [ 13 ], 86 nM for Liu-20 [ 30 ], 711 nM for PF-4800567 and CK1δ as well as 32 nM for PF-4800567 and CK1ε [ 13 ] (see Table 2 ). Apart from the possible occurrence of batch-to-batch variability for the tested SMIs (which is beyond the scope of this manuscript and will not be discussed further), these differences might arise because the initial velocity region for performing in vitro kinase reactions has not been determined properly, or a differentiation between substrate phosphorylation and autophosphorylation has not been possible due to assay design and the analysis of total phosphorylation events, as this was the case for the previous determination of IC 50 values for PF-670462 and PF-4800567 [ 13 ].…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…When comparing the IC 50 data provided in Table 2 , it has to be considered that, as expected, our calculated IC 50 values for PF-670462, Liu-20 and PF-4800657 differ from the previously published IC 50 values of 13 nM for PF-670462 and CK1δ [ 13 ], 86 nM for Liu-20 [ 30 ], 711 nM for PF-4800567 and CK1δ as well as 32 nM for PF-4800567 and CK1ε [ 13 ] (see Table 2 ). Apart from the possible occurrence of batch-to-batch variability for the tested SMIs (which is beyond the scope of this manuscript and will not be discussed further), these differences might arise because the initial velocity region for performing in vitro kinase reactions has not been determined properly, or a differentiation between substrate phosphorylation and autophosphorylation has not been possible due to assay design and the analysis of total phosphorylation events, as this was the case for the previous determination of IC 50 values for PF-670462 and PF-4800567 [ 13 ].…”
Section: Discussionsupporting
confidence: 52%
“…According to our workflow with the aim of determining comparable parameters for SMIs, IC 50 values for GST-CK1δ and 6×His-CK1δ were determined using the defined initial velocity conditions and an ATP concentration equivalent to the calculated K m (ATP) values. As appropriate examples for previously reported and established SMIs the CK1-specific ATP-competitive inhibitors PF-670462 [ 12 ] and Liu-20 [ 30 ] were used for determination of IC 50 values ( Figure 8 and Table 2 ). The determined IC 50 values show high comparability between GST- and 6×His-tagged CK1δ: IC 50 values were calculated with 69.85 nM (PF-670462) and 395.80 nM (Liu-20) for GST-CK1δ and 64.18 nM (PF-670462) and 403.60 nM (Liu-20) for 6×His-CK1δ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the anti-tumor efficacy of CK1 inhibition, for example, it has been shown that CK1δ/ε inhibitors with low nanomolar IC 50 s demonstrated efficacy in vitro and in preclinical in vivo models of breast cancer (e.g., SR-3029 [46]). Some CK1 inhibitors proved to have higher efficacy on mutant CK1 variants (e.g., CK1δ mutants in colon cancer [47]), which may be beneficial as a form of personalized medicine. These preclinical studies have involved both in vitro and in vivo stages of testing, and a number of structurally different compounds.…”
Section: Ck1 Inhibitors and Their Therapeutic Potential In Hematologimentioning
confidence: 99%
“…Preclinical studies have identified potential targets for therapy, opening up new avenues for the development of novel treatment strategies [16][17][18][19][20]. Moreover, the regulation of EGFR expression by VEGFR signaling has been demonstrated [21], suggesting possible implications for the clinical use of anti-EGFR and anti-VEGF drugs.…”
mentioning
confidence: 99%